Narrative Stimulation in Jahiliyyah Novel - Al-Shahrani, Nora Saad Mohammed (Arts for Linguistic & Literary Studies, 2023)
This paper examines Laila Al-Juhani's novel Jahiliyyah ‘Ignorance’ and focuses on the mechanisms of narrative incentives within the novel. The paper aims to understand how these incentives contribute to the conflict in the novel's structure and its overall implications. It identifies three types of narrative incentives: contextual, characteristic, and objective motivation. The novel uses textual transcendentalism and parallel texts to motivate its characters, with negative patterns outweighing positive ones. The linguistic structure of the novel is closer to societal deliberation in daily life than literary language, with verbal associations drawn from pragmatic linguistic contexts. Understanding the linguistic structure and narrative formation helps to measure the literary text of the novel and transform the story into an amazing narrative structure through the formation of incentives. Overall, the paper helps readers understand the narrative techniques and linguistic structures employed in the novel to create a captivating story.